Análise de custos do transporte fluvial de passageiros na Amazônia: estudo de caso em uma embarcação no trecho Parintins-AM/Nhamundá-AM/Faro-PA. - Tavares, Hakkinen Souza (Brasil, 2025)
Cost management is fundamental to a company's stability and financial health, allowing it to grow and compete in the market, helping to define competitive prices for products or services, which in turn makes it possible to define the company's profitability. To do this, a company needs to understand which costs are linked to its operations, which can be done through analysis and technical surveys. However, for companies in the river passenger transportation sector, defining the costs linked to the operation of vessels becomes challenging when some variables are taken into account, such as the seasonality of the rivers and the lack of financial records, as well as market competition and the quality of the service offered. Against this backdrop, this study analyzes the costs related to the passenger transport service of a vessel that operates the Parintins-AM/Nhamundá-AM/Faro-PA route. Initially, cost analysis methodologies for air, land and river transportation were researched. Next, a case study was planned to evaluate the costs of a river vessel based on an academic methodology, using real data collected from the vessel. As a result, it was concluded that fixed costs represent 57.61% of total costs, with labor costs accounting for 63.7% of this amount. Variable costs represent 42.3% of total costs, with fuel accounting for 88.37%. The study also defined the cost per passenger for each period in which the boat makes its trips, helping the owner to define the price to be charged regardless of the seasonality of the rivers.